Pathology in the Process of Governance at the Local Government Level - Janowska, Zdzisława (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Pathology in the process of governance in local government is a fact. It bases on the results of representative surveys of public Supreme Chamber of Control (NIK) and on opinions some officials in this regard. This paper presents a diagnosis, examples of pathological activities and highlights the role of social unmasking activity "in good faith". Some proposal of changes were formulated which would have a chance to change the status quo.